Hubungan Pengetahuan Dan Sikap Masyarakat Terkait Praktik Pemilihan Obat Herbal Yang Halal Di Apotek Farmarindo - Rosyid, Abdur; Kulsum, Ummi; Priyatno, Sugeng (Indonesian Journal of Medical and Pharmaceutical Science, 2024)
Background: For Muslims, whether a drug is not known whether it is halal or not is fundamental because the law on drug consumption is the same as food consumption, namely that all drugs must be halal. Good knowledge and attitude towards the practice of selecting halal drugs is very important for a Muslim because drugs containing elements of carrion, blood and pork are not permitted. The aim of this study are to know the relationship between knowledge and public attitudes regarding the practice of selecting halal herbal medicines in Farmarindo Pharmacy. Methods: This research is a descriptive study with a cross sectional approach used purposive sampling techniques and Lemeshow formula calculations. Data analysis used the Spearman test. Results: The category of knowledge of halal herbal medicines at the Farmarindo Banyumas Pharmacy was 85% in the good category and 15% in the sufficient category. The attitude category was 61% in the good category, and 39% in the bad category. Meanwhile, in the practice category, 66% were in the good category and 34% were in the bad category. Conclusion: There is a relationship between knowledge and public attitudes regarding the practice of selecting halal herbal medicines in pharmacies. Where the significant values are between knowledge and community attitudes (0.564**), knowledge and the practice of selecting halal herbal medicines (0.346**), and community attitudes and the practice of selecting halal herbal medicines (0.420**).